[PP.36.26]: EVALUATION OF LEFT ATRIUM CONTRACTILE FUNCTION FOR PAROXYSMAL ATRIAL FIBRILLATION PREDICTION IN HYPERTENSIVE PATIENTS WITH ACUTE MYOCARDIAL INFARCTION. (June 2015) - Toader>, D.>; Racareanu, A.; Mihailovici, A.; Musetescu, R.
Abstract : Objective: Atrial mechanical dysfunction is correlated to paroxismal atrial fibrillation (PAF) prevalence. A' wave velocity of mitral annulus evaluated with tissue Doppler echocardiography is linked to left ventricle diastolic pressure (LVEDP). Purpose of the study was to find a correlation between LA contractile dysfunction evaluation using tissue Doppler echocardiography and the risk of PAF during first week of acute myocardial infarction (AMI) in hypertensive patients. Design and method: 98 hypertensive patients (56 males and 42 females), admitted with AMI with ST-segment elevation were evaluated during the first week by: clinical examination, 12 lead standard ECG, echocardiographic measurements of: left ventricle mass index (LVMi); cut off values for left ventricular hypertrophy (LVH) were LVMi > 115 g/m2 in males and > 95 g/m2 in females; pulsed tissue Doppler echocardiography of mitral valve ring was used for mean values A wave velocities evaluation. Normal median values were 10 ± 2 cm/s. Standard deviation (SD) and coefficient of variation (CV) were calculated. LVEF measured by Simpson method was less than 45%. All patients received fibrinolytic therapy. Patients were in sinus rhythm, without history of prior AMI, valvular heart disease or PAF. 24 hours monitoring using Holter recordings were used for PAF detection. Patients were divided in 4 groups: 1.LVH+ and reperfusion 2.LVH+ without reperfusion 3.LVH- and reperfusion 4.LVH- without reperfusion. Results: 1.LVH was find in 68, 36% of patients. 2.Velocities mean values at lateral corner of mitral ring: A' = 8, 62 cm/s; SD:1, 00, CV:11, 85 in cases with LVH without reperfusion and 8, 32 cm/s in those without LVH and with successful fibrinolysis; SD:0, 96, CV:11, 31. 3.At medial corner: A" = 8, 54 cm/s in cases with LVH without reperfusion; SD:1, 13, CV:13, 92 and 7, 03 cm/s in those without LVH and with successful fibrinolysis, SD:1, 34, CV:15, 68. 4.Incidence of PAF was: 55, 01% in patients with A' mean values > 8, 62 cm/s compare to 11, 22% in those with A' mean values<8, 32 cm/s and 42, 85% in patients with A" mean values > 8, 54 cm/s compare to 8, 16% in those with A" mean values<7, 03 cm/s. Conclusions: 1.A' and A" waves mean values were higher in hypertensive patients with LVH without reperfusion. 2.LA contractile function evaluation using tissue Doppler echocardiography predicted the risk of PAF during first week of myocardial infarction in hypertensive patients.